Systemic overexpression of interleukin-22 induces the negative immune-regulator SOCS3 and potently reduces experimental arthritis in mice - Aarts, Joyce (Rheumatology (Oxford), 2020)
OBJECTIVE: High levels of IL-22 are present in serum and synovial fluid of patients with RA. As both pro- and anti-inflammatory roles for IL-22 have been described in studies using animal models of RA, its exact function in arthritis remains poorly defined. With this study we aimed to further unravel the mechanism by which IL-22 exerts its effects and to decipher its therapeutic potential by overexpression of IL-22 either locally or systemically during experimental arthritis. METHODS: CIA was induced in DBA-1 mice by immunization and booster injection with type II collagen (col II). Before arthritis onset, IL-22 was overexpressed either locally by intra-articular injection or systemically by i.v. injection using an adenoviral vector and clinical arthritis was scored for a period of 10 days. Subsequently, joints were isolated for histological analysis of arthritis severity and mRNA and protein expression of various inflammatory mediators was determined in the synovium, spleen and serum. RESULTS: Local IL-22 overexpression did not alter arthritis pathology, whereas systemic overexpression of IL-22 potently reduced disease incidence, severity and pathology during CIA. Mice systemically overexpressing IL-22 showed strongly reduced serum cytokine levels of TNF-α and macrophage inflammatory protein 1α that correlated significantly with the enhanced expression of the negative immune regulator SOCS3 in the spleen. CONCLUSION: With this study, we revealed clear anti-inflammatory effects of systemic IL-22 overexpression during CIA. Additionally, we are the first to show that the protective effect of systemic IL-22 during experimental arthritis is likely orchestrated via upregulation of the negative regulator SOCS3.